Screening of dandelion phenolic extracts and their anti-bacterial function against Escherichia coli through acting on Na+-K+ ATPase - Pujun Xie; Xiang Wang; Lixin Huang; Yejun Deng; Caihong Zhang (Food Production, Processing and Nutrition, 2024)
Abstract Food contamination by Escherichia coli (E. coli) is an increasing public health concern. Screening for natural plant preservatives has received increasing attention. In this study, dandelion flower phenolic extract (DFPE), with the strongest bacterial inhibition and the highest polyphenol level from various organs, was identified using HPLC and FTIR. The results showed a significant increase in extracellular ATP levels due to cellular membrane leakage in E. coli and decreased Na+-K+ ATPase activity. These behaviors were caused by representative phenolic compounds such as caffeic acid in DFPE. Molecular docking simulations were performed to reveal the mechanism of interaction between caffeic acid and Na+-K+ ATPase. This indicated that conventional hydrogen bonds, pi-anions, and pi-alkyl were involved in the interaction between them. Molecular dynamic equilibrium of the liganded ATPase complex was achieved after 20 ns. The lower values of Rg and SASA demonstrated that the liganded ATPase structure changed from a relatively loose to a tight state in the presence of caffeic acid. Overall, these findings are meaningful for screening bioactive compounds from various food-derived plant tissues using a combination of practical experimentation and molecular simulations. Graphical Abstract